2019
DOI: 10.4028/www.scientific.net/kem.822.473
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Titanium Powders and Products Manufactured by the Direct Laser Deposition Method

Abstract: Ti-6Al-4V powders from two different vendors and two different fraction were compared with respect to their microstructures, size-distributions, chemistries, surface appearances. In addition, the influence of these powders on the structure and properties of products manufactured by an additive direct laser deposition method were established. The main parameters that have a significant impact on the structure and properties of Ti-6Al-4V deposited parts were established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results of the study of L-DED material obtained from the considered powders showed that the most significant influence is exerted by light impurities in the powder [18]. Figure 17 shows that powder B1 has an increased hydrogen content.…”
Section: Input Control Of Titanium Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study of L-DED material obtained from the considered powders showed that the most significant influence is exerted by light impurities in the powder [18]. Figure 17 shows that powder B1 has an increased hydrogen content.…”
Section: Input Control Of Titanium Alloysmentioning
confidence: 99%
“…Particle size distribution also can affect the size factor of the structure, for example, the grain size. In the work of the authors present results [18] of powder size influence on the grain size for L-DED Ti-6Al-4 V titanium alloy (Figure 7). Wide powders fraction is also undesirable for an L-DED process.…”
Section: Metal Powder Materials For the Dld Process Requirements 21 S...mentioning
confidence: 99%